PENDIDIKAN ISLAM PADA MASA AWAL KEMERDEKAAN INDONESIA (KONTESTASI IDEOLOGI DAN GAGASAN) - Rinatul Khumaimah (LPPM Institut Agama Islam Al-Hikmah Tuban, 2021)
Abstract. The development of religious education after Indonesia's independencereceived serious attention from the government, both in public and private schools.Efforts for this began by providing assistance to institutions as recommended by theWorking Body of the Central National Committee (BPKNP) December 27, 1945. Eventhough Indonesia had just proclaimed its independence and was facing a physicalrevolution, the Indonesian government had made improvements by paying attention tothe issue of education which was considered quite important, so that formed theMinistry of Education, Teaching and Culture PP and K).Keyword: Islamic Education, The Begining Of Freedom